Transduction of a plasmid containing the bacteriophage D3 cos site in Pseudomonas aeruginosa. - Sharp, R (1990)
Plasmids harboring the cos sequences of bacteriophage D3 can be transferred, by bacteriophage D3, into Pseudomonas aeruginosa by a mechanism which is insensitive to DNase. Transducing activity was separated from the plaque-forming particles by CsCl equilibrium gradient centrifugation. Restriction endonuclease digestion patterns suggest that the transducing particles contain plasmid concatemers.